Surgical resection of retrorectal tumours in adults: long‐term results in 47 patients. (29th August 2013) - Chéreau, N.; Lefevre, J. H.; Meurette, G.; Mourra, N.; Shields, C.; Parc, Y.; Tiret, E.
Abstract Aim Retrorectal tumours (RT) are uncommon, and diagnosis and management remain difficult. The aim of this study was to evaluate the results of the surgical management of RT in our institution. Method Medical notes of all patients operated on for RT were reviewed. Clinical, radiological, surgical, histological data as well as morbidity and long‐term results were noted. Results Forty‐seven patients [34 women (72%), mean age 45.8 (range 17–85) years] underwent surgery for RT between 1997 and 2011. The commonest symptoms were pain (n = 31) and suppuration (n = 10). Thirty‐nine (83%) patients underwent preoperative magnetic resonance imaging (MRI). Malignant lesions exhibited typical characteristics on MRI including heterogeneity (n = 5, 83%), solid appearance (n = 4, 67%), a low‐T1 signal and high‐T2 intensity (n = 5, 83%), enhancement after gadolinium injection (n = 5, 83%), irregular margin (n = 4, 67%) and extension above S3 (i = 5, 83%). A Kraske approach was used in 42 (89%) patients with resection of the coccyx in 25 (60%) and an abdominal or combined approach for the remaining five. Four patients developed complications (two haematoma, two abscess), but only one (haematoma) required reoperation. Histological examination showed 38 (80.9%) benign lesions. After a median follow‐up of 71 (2–168) months, 5‐year disease‐free survival was 75% for malignant lesions and 93.1% for benign lesions (P = 0.023). Four (4/42; 9.5%) patients had moderate perineal pain after a Kraske approach, while no anal dysfunction was seen. Conclusion Magnetic resonance imaging was the most helpful investigation for retrorectal tumours. The posterior trans‐sacrococcygeal approach is the procedure of choice for complete resection for most, especially for benign and cystic lesions without extension above S2.